The cost of quality in Internet-style networks. - Dutta-Roy, A. (IEEE spectrum)
In broad terms, the quality of service (QoS) of a wide-area network is a measure: of how well it does its job-how quickly and reliably it transfers various kinds of data, including digitized voice and video traffic, from source to destination. With the advent of packet switching and the proliferation of many kinds of communications traffic (time-sensitive financial transactions, still images, large data files, voice, video, and so on), there are more than one set of criteria to satisfy. The the data rate needed for satisfactory voice communication may take an intolerable time to transfer high-resolution images. Conversely, the degree of network latency acceptable in transferring some files may not be adequate for real-time voice. So QoS has become a hot topic, and the contracts that specify it, called service level agreements (SLAs), are becoming more and more common, at least between service providers and their largest customers. As incumbent providers of telecommunications service are increasingly being challenged by competitive carriers, QoS has become a convenient marketing tool for both. The ability truly to deliver quality of service will separate the winner from the losers in the packet-switched future. The paper defines QoS, its priorities, and improvement